Роман-алегореза Олега Сича "Uroboros" - Бовсунівська, Т. (Слово і Час, 2014)
У статті йдеться про жанрові особливості роману-алегорези Олега Сича “Uroboros”, які
розкриваються в контексті традиційних та сучасних теорій алегорії. Алегореза виступає
природною формою людського мислення тому, що в ній схоплений принцип регулярності –
зіставлення сюжету та його проекції на основі аналогій. Роман-алегореза – одна з модифікацій
параболічного роману. Розгортання езотеричних сенсів роману “Uroboros” до вивершеної
алегорези побудоване на “Тибетській книзі мертвих” та сучасних психоаналітичних теоріях,
насамперед Еріха Нойманна. The article deals with the genre specifics of the allegorical novel “Uroboros” by Oleh Sych which
is analyzed against the backdrop of traditional and modern theories of allegory. Allegory is assumed
to be a natural form of human thinking, since it employs the regularity principle, particularly in form
of analogies which juxtapose the plot of the novel and its projections. Allegorical novel is one of the
several modifi cations of parabolic novel. The esoteric meanings of the novel “Uroboros” which are
being summed up into perfect allegory are based upon “The Tibetan Book of the Dead”, as well as
on contemporary psychoanalytic theories, especially that by Erich Neumann. Статья посвящена жанровым особенностям романа-аллегорезы
Олега Сыча “Uroboros”, которые раскрываются в контексте
традиционных и современных теорий аллегории. Аллегореза –
естественная форма человеческого мышления, поскольку в ней
отражается принцип регулярности – сопоставление сюжета и его
проекции на основе аналогий. Роман-аллегореза является одной
из модификаций параболического романа. Развитие эзотерических
смыслов романа “Uroboros” до завершенной аллегорезы опирается
на “Тибетскую книгу мертвых” и современные психоаналитические
теории, прежде всего, Эриха Нойманна.